THE EFFECTIVENESS OF THE BUSINESS COMPETITION SUPERVISORY COMMISSION IN HANDLING CASES OF ALLEGED UNFAIR BUSINESS COMPETITION CONDUCTED BY PT AERO CITRA CARGO - Wike Nopianti; deny guntara; muhamad abas (JHR (Jurnal Hukum Replik), 2023)
Allegations of a monopoly on the export of apparent lobster seeds originated from a case of corruption in evident lobster seeds committed by former Minister of Maritime Affairs and Fisheries Edhy Prabowo. In the indictment filed by the Public Prosecutor, Edhy allegedly founded and managed the Aero Citra Kargo Limited Liability Company as a shell company to collect profits from the export of apparent lobster seeds. At that time, the Business Competition Supervisory Commission suspected that the Aero Citra Kargo Limited Liability Company violated 17 and 24 of Law Number 5 of 1999. This study aimed to determine the effectiveness of the Business Competition Supervisory Commission in handling cases of alleged unfair business competition carried out by the Aero Citra Kargo Limited Liability Company. And to find out the considerations of the Commission Council for the Supervision of Business Competition in deciding Case Number 04/Commission for the Supervision of Business Competition-I/2021. This scientific research uses normative qualitative research methods. The author uses a normative juridical strategy in this approach. The Commission for the Supervision of Business Competition has played an influential role in cases of unfair business competition/monopoly practices, especially in cases of unfair business competition for export shipping services for Clear Lobster Seeds carried out by Aero Citra Kargo Limited Liability Company, the Commission Council has correctly determined decision dictum based on facts, judgment, analysis, and conclusion. The Commission Council only provides sanctions in the form of stopping activities carried out by the Aero Citra Cargo Limited Liability Company, which following the legal basis, namely Law No. 5 of 1999Keywords: Effectiveness, Monopolistic Practices, export